2016
DOI: 10.1371/journal.ppat.1006067
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Staphylococcus aureus TarS, the Wall Teichoic Acid β-glycosyltransferase Involved in Methicillin Resistance

Abstract: In recent years, there has been a growing interest in teichoic acids as targets for antibiotic drug design against major clinical pathogens such as Staphylococcus aureus, reflecting the disquieting increase in antibiotic resistance and the historical success of bacterial cell wall components as drug targets. It is now becoming clear that β-O-GlcNAcylation of S. aureus wall teichoic acids plays a major role in both pathogenicity and antibiotic resistance. Here we present the first structure of S. aureus TarS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 86 publications
(99 reference statements)
2
64
1
1
Order By: Relevance
“…The functions of DltB and DltD are not as clear but are thought to transport the DltC-D-Ala intermediate across the membrane and subsequently D-alanylate TA acceptor substrates. Glycosylation of TAs has remained relatively underexamined by comparison, but recent studies have made progress in demonstrating the roles of TarM and TarS in transferring ␣and ␤-GlcNAc, respectively, to WTA in S. aureus (24)(25)(26)(27). WTA modification with ␤-GlcNAc imparts beta-lactam resistance, is critical to colonization, and plays a role alongside D-Ala modifications in cell division and morphogenesis (28,29).…”
Section: Importancementioning
confidence: 99%
“…The functions of DltB and DltD are not as clear but are thought to transport the DltC-D-Ala intermediate across the membrane and subsequently D-alanylate TA acceptor substrates. Glycosylation of TAs has remained relatively underexamined by comparison, but recent studies have made progress in demonstrating the roles of TarM and TarS in transferring ␣and ␤-GlcNAc, respectively, to WTA in S. aureus (24)(25)(26)(27). WTA modification with ␤-GlcNAc imparts beta-lactam resistance, is critical to colonization, and plays a role alongside D-Ala modifications in cell division and morphogenesis (28,29).…”
Section: Importancementioning
confidence: 99%
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram-positive bacteria, 76 and between the peptidoglycan and the outer membrane of the Gramnegative bacteria. 77,78 Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram-positive bacteria 69,[79][80][81][82][83][84] and with respect to lipopolysaccharide transport in Gram-negative bacteria. [85][86][87][88][89][90] Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope-targeting Antibioticsmentioning
confidence: 99%
“…Moreover, the GP12 trimer has the capacity to accommodate multiple polymeric substrates (27), a property associated with processively acting enzymes (45). Even so, taking into account that GP12 catalyzes two distinct hydrolytic reactions, it would seem that non-processive polymer degradation is a likely mode of action for this enzyme.…”
Section: Tablementioning
confidence: 99%